Managing the Impact of Smoke Haze Disaster: Response of Civil Society Groups Towards Jambi Provincial Government Performance - Arfan, Arfan (Jurnal Bina Praja, 2016)
Smoke haze from forest and land fires in Jambi in 2015 had led to various reactions. The low response from the provincial government led by an Acting Governor received various criticism and protests from civil society groups. This study examines the impact of 2015â€™ haze in Jambi and describes civil society groupsâ€™ responses toward the government â€œtransitionâ€ of Jambi province performances regarding 2015 smoke haze. Through observation of the relation and activities of the two sides: government and civil society, and open-ended interview with a representative of civil society groups, the results showed that the barrier is the absence of a national disaster status. Acting Governor and Regional Working Unit (SKPD) have a limitation in funding, equipment, and human resources to conduct fire fighting and are unresponsive in treating the haze victims. The persistence of civil society groups which work independently to helpvictims and encourage the government to be more responsive led to the issuance of Local Regulation on Forest and Land Fires. Finally, this study recommends the government of the Republic of Indonesia to formulate task and function certainty of the central government and Acting Governor in the handling of smoke haze under the condition withoutnational disaster status.